2003
DOI: 10.1577/1548-8659(2003)132<0120:iofpoa>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Fish Predation on Assemblage Structure of Macroinvertebrates in an Intermittent Stream

Abstract: Ahstrucf.-Despite considerable investigation of stream systems, the influence of fish predation on macroinvertebrate assemblages is still poorly understood and remains a controversial subject. We conducted a field experiment in an intermittent reach of Alum Creek in the Ouachita Mountains, Arkansas, to examine the effects of predatory fish on macroinvertebrate assemblages. We tested the prediction that with pool isolation fish would have a top-down influence on macroinvertebrate assemblages. Overall, fish had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
44
1
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(50 citation statements)
references
References 39 publications
4
44
1
1
Order By: Relevance
“…The importance of BM as an autochthonous food resource for fishes in rivers and streams is well documented in the literature (PREJS & PREJS 1987, LOBON-CERVIÁ & BENNEMANN 2000, ABELHA et al 2001, ABES et al 2001, CALLISTO et al 2002b, CASATTI 2002, WILLIAMS et al 2003, POUILLY et al 2004.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…The importance of BM as an autochthonous food resource for fishes in rivers and streams is well documented in the literature (PREJS & PREJS 1987, LOBON-CERVIÁ & BENNEMANN 2000, ABELHA et al 2001, ABES et al 2001, CALLISTO et al 2002b, CASATTI 2002, WILLIAMS et al 2003, POUILLY et al 2004.…”
Section: Discussionmentioning
confidence: 94%
“…According to WILLIAMS et al (2003), some fish species show feeding preferences for special benthic organisms, independent of their abundance and presence in the sediment. Seasonality and human activities affect the density and richness of BM communities (BISPO & OLIVEIRA 1998, CALLISTO et al 2005, a fact that can justify the feeding plasticity common of freshwater fishes (ABELHA et al 2001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To characterize the aquatic habitat of each sample stream reach, channel substrate type (percentages of sand, silt, gravel, cobble, and boulder) was estimated visually within a 1 m wide area of stream channel bottom at the end of each segment (0, 33, 66, and 100 m) and averaged for the entire stream reach (Williams et al 2003a). The proportion of large wood habitat was estimated visually for each segment and averaged for the entire stream reach.…”
Section: Aquatic Habitatmentioning
confidence: 99%
“…For example, Nicola et al (2010) claimed that in streams, benthic communities are most affected by water chemistry, and less by fish predation. On the other hand, Williams and Taylor (2003) found a significant influence of fish predations on the density and taxonomic structure of invertebrates in isolated pools of an intermittent stream. Moreover, Bonneau and Scarnecchia (2015) found that Cyprinus carpio can cause impoverishment of the macroinvertebrate taxa richness in streams.…”
Section: Discussionmentioning
confidence: 96%